Pemilihan dan Perawatan Baling-Baling Penggerak Perahu Nelayan Kec. Maros Baru - ., Baharuddin; Muhammad, A. Haris; Nikmatullah, Muh. Iqbal; Sitepu, Andi Husni; Rivai, Hariyanti; Shintarahayu, Balqis; Klara, Syerly; ., Zulkifly; Alwi, Rusydi; Hariyanto, Surya (Faculty of Engineering UNHAS, 2025)
The ship's driving system and propeller are components of the ship's propulsion device, and although they have been made in such a way and are strong, they will be damaged along with their service life. Damage to the propeller blades due to cavitation will have an impact, triggering noise and vibrations, and it will be the leading cause of decreased propeller thrust. Low ship propulsion efficiency increases fuel costs, making the ship unseaworthy and less efficient. Broken propeller blades when the ship is at sea threaten the safety of the ship and threaten the safety of the fishermen's lives. From the above conditions, the 2024 LBE-Collaboration PPM Program was held to provide counseling to members of the target fishermen group,